FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN SUBYEKTIF AKIBAT DEBU PADA PEKERJA PENGGILINGAN PADI DI KECAMATAN SUKOWONO KABUPATEN JEMBER - Prahastuti S., Anita Dewi; Ratinasari, Maretta (FKM - UNEJ, 2011)
In rice mill industry, there are a number of risks that lead to health problems to workers. One of the problems is dust resulted from the process of milling paddy to become rice. Dust can decrease air quality and produces air pollution.District of Sukowono, Jember Regency is one of rice production centres in Jember Regency. Based on preliminary survey on October 7, 2009, 8 of 20 workers at rice mills in District of Sukowono often experienced subjective complaints. The complaintsÂ felt by the workers were itch on skin, eyesore, cough, short-winding, itch in throat and sneezing. This research is intended to analyze factors related with subjective complaints caused by dust on rice mill workers in District of Sukowono, Jember Regency. This research applied analytic-observational method by cross-sectional approach. The research was conducted at PB. Lahan Mas and UD. Wringin Jaya, District of Sukowono, Jember Regency, from December 2009 to January 2010. The population in this research was 155 people and samples were 60 persons. Data analyses applied by the researcher were Spearman Test and Contingency Coefficient Test in purpose of identifying the relation between individual characteristics, dust concentration and dust control due to subjective complaints on workers at rice mills. Based on statistical test, it was obtained that there was correlation between age (p=0.007), length of work period (p=0.000), smoking habit (p=0.040), personal hygiene (p=0.000) and dust concentration (p=0.011) and subjective complaints of breathing. Moreover, sex (p=0.425), level of education (p=0.140), length of work period (p=0.159), exercising habit (p=0.370), the usage of personal protective equipment (p=0.775) did not have correlation with subjective complaints of breathing. From the research results, it is expected that workers reduce cigarette consumption and not smoke while working. Furthermore, to rice mill owner, it is expected that they pay attention to interior matters such as cleaning place of work from dust of rice milling on floor, wall and milling equipment routinely every work day and conduct an inspection on the cleanness and tidiness of workplace, provide personal protective equipment, especially masker to reduce dust inhalation which minimizes breathing complaints, give sanctions to workers who smoke in their job. Keywords: subjective complaints caused by dust, rice mill workers